Fulminant development of a giant pelvic metastasis from microsatellite-stable early-onset sigmoid colon cancer with KRAS and TP53 co-mutations: a case report - Shouxin Wei; Sijia Yu; Yunsheng Lan (Frontiers in Medicine, 2026)
Background Early-onset colorectal cancer (EO-CRC) is often characterized by a highly aggressive nature and insidious onset. Herein, we report a rare case of fulminant, early-onset colon cancer presenting with a massive pelvic seeding metastasis driven by concurrent KRAS and TP53 mutations. This study aims to elucidate the molecular mechanisms underlying its hyper-progressive course and provide critical insights into clinical differential diagnosis. Case description A 44-year-old female presented with intermittent abdominal pain for 8 months, which worsened alongside abdominal distension for 10 days prior to admission. Notably, an abdominopelvic CT scan performed 8 months earlier had yielded unremarkable findings. Upon admission, laboratory evaluations revealed a fulminant elevation of serum tumor markers (CEA: 256.63 ng/mL, CA19-9: 3,724.63 U/mL), and an abdominopelvic CT, subsequently confirmed intraoperatively, revealed a massive (~20 cm) cystic-solid pelvic mass accompanied by 1,000 mL of ascites. The primary lesion was identified as a 3.1 cm sigmoid colon adenocarcinoma. The patient successfully underwent combined radical resection. Postoperative histopathology confirmed that the pelvic mass was a metastasis originating from the colon adenocarcinoma [CDX2 (+), CK20 (+)], exhibiting lymphovascular invasion and intermediate tumor budding (Grade Bd2). Next-generation sequencing (NGS) demonstrated that the tumor was microsatellite stable (MSS) and harbored concurrent pathogenic mutations in KRAS (p.G12D, 28.70%) and TP53 (p.I195T, 42.50%), conferring intrinsic resistance to conventional anti-EGFR monoclonal antibodies and immunotherapy. Consequently, a multidisciplinary team (MDT) formulated a therapeutic strategy consisting of systemic adjuvant chemotherapy with bevacizumab plus mFOLFOX6, paired with high-frequency follow-up. Conclusion Early-onset MSS colorectal cancer, driven by concurrent KRAS/TP53 mutations, can exhibit extreme, hyper-progressive malignant behavior. A recent negative screening result cannot entirely rule out the development of interval colorectal cancer. Clinicians must maintain a high index of suspicion for primary gastrointestinal malignancies when encountering massive cystic-solid pelvic masses in female patients. Timely multi-gene NGS panel testing is crucial to deciphering multi-drug resistant oncogenic driver axes and tailoring individualized precise treatment strategies.